Electrolyte for regulating interface reaction based on organic anion mediated gradient ion pump
By using an organic anion-mediated gradient ion pump to regulate the interfacial reaction of the electrolyte in a zinc metal battery, an organic/inorganic hybrid SEI layer is formed, which solves the problem of poor cycle stability of the zinc anode, achieves high reversibility and long cycle life, reduces side reactions and interfacial resistance, and improves the overall performance of the zinc metal battery.
Patent Information
- Application Number
- CN202511581164.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2025-12-19
AI Technical Summary
The poor cycle stability of zinc anode in zinc metal batteries is mainly due to side reactions caused by zinc dendrite growth and interfacial active water, which lead to an imbalance in the interfacial ion concentration field and corrosion of the zinc anode. The low conductivity of existing organic components makes it difficult to balance the contradiction between interfacial resistance and efficient ion migration.
An electrolyte based on an organic anion-mediated gradient ion pump to regulate interfacial reactions is employed, comprising a mixed aqueous solution of zinc salt electrolyte and organic anion salt. Through electrostatic binding of organic anions with the zinc surface, hydroxyl groups regulate the uniform flux of Zn2+, and hydrophobic alkyl groups repel free water molecules, an organic/inorganic hybrid layered SEI is formed. The outer layer is an amorphous organic/ZnCO3 layer, and the inner layer is an organic/ZnCO3/ZnO/ZnS layer, achieving rapid zinc ion transport and suppression of side reactions.
It significantly improves the reversibility and cycle life of zinc anodes. The average coulombic efficiency of zinc//Ti asymmetric cells is greater than 99%, the cycle life of Zn//Zn symmetric cells exceeds 2000 hours, and Zn//MnO2 full cells are stable at high rates. The side reaction suppression effect is significant, the interface resistance is reduced, and the cost is low and easy to scale up.
Smart Images

Figure CN121172297A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc metal batteries, and more specifically to an electrolyte based on an organic anion-mediated gradient ion pump that regulates interfacial reactions. Background Technology
[0002] Aqueous zinc metal batteries (AZMBs), as a safer alternative to alkali metal batteries, have attracted widespread attention in the energy storage field. However, the lifespan of AZMBs is limited by the cycle stability of the zinc anode. The failure modes of the zinc anode mainly manifest as zinc dendrite growth and side reactions induced by interfacial active water. Studies have shown that the main cause of zinc anode failure stems from the contradiction between the rapid electrochemical reaction kinetics and the slow zinc ion mass transfer kinetics within its interfacial electric double layer. These kinetic differences lead to the rapid consumption of zinc ions within the electric double layer, causing an imbalance in the interfacial ion concentration field and initiating uneven zinc ion nucleation and epitaxial growth processes. This difference is particularly significant under high-rate testing conditions. Furthermore, in aqueous electrolytes, the inherent thermodynamic instability of zinc metal, such as the zinc ion reduction potential being -0.763 V relative to the standard hydrogen electrode, results in a competitive hydrogen evolution reaction during the zinc ion reduction and deposition process, leading to spontaneous or electrochemical corrosion of the zinc metal anode. Meanwhile, the hydrogen evolution reaction causes hydroxide ions to accumulate at the zinc anode interface. These hydroxide ions combine with other surrounding ions to form by-product deposits with low conductivity and loose structure (such as Zn4SO4(OH)4・xH2O), which further increases the interfacial resistance of the zinc anode, exacerbates zinc anode corrosion, and continuously consumes electrolyte.
[0003] A fundamental limitation of AZMBs is their inability to spontaneously form a stable solid electrolyte interphase (SEI), which is crucial for mitigating this problem. Based on this, researchers have adopted various strategies, including functionalized membranes, artificial interphase layers, and electrolyte engineering. Among these, electrolyte engineering has emerged as a simple and practical method. Its mechanisms include regulating zinc ion flux, optimizing nucleation sites, establishing electrostatic shielding layers, and inducing preferred crystal facet deposition. The synergistic effect of these mechanisms is effective for constructing uniform SEIs in situ. A smooth SEI layer can homogenize the interfacial electric field and ion concentration field, playing a crucial role in regulating interfacial reactions. However, during cyclic zinc deposition / stripping, significant fluctuations in the interfacial microenvironment (such as pH and byproduct accumulation) can lead to SEI instability, manifested as swelling or peeling, making it impossible to maintain long-term equilibrium and stability at the electrode / electrolyte interface. Therefore, exploring the construction of organic / inorganic hybrid SEI layers using organic functional groups is crucial, as these SEIs exhibit superior interfacial affinity and ion transport efficiency. More importantly, the chemical bonding between organic functional groups and inorganic components can enhance the SEI network's adaptability to mechanical stress / strain during zinc deposition / stripping. Nevertheless, the inherently low electrical conductivity of organic components makes it difficult to balance the contradiction between interfacial resistance and efficient ion migration, severely hindering the development of functionalized SEIs containing organic components. Summary of the Invention
[0004] To solve the above-mentioned technical problems, the solution of the present invention is as follows:
[0005] An electrolyte based on an organic anion-mediated gradient ion pump to regulate interfacial reactions, wherein the electrolyte comprises a mixed aqueous solution of a zinc salt electrolyte and an organic anion salt.
[0006] The zinc salt electrolyte is selected from any one of zinc sulfate, zinc chloride, zinc acetate, or zinc trifluoromethanesulfonate.
[0007] In organic anionic salts, the organic chain has a Janus structure and contains hydroxyl groups and hydrophobic alkyl groups at the end of the chain.
[0008] In the technical solution provided by this invention, organic anions electrostatically bind to the zinc surface, and hydroxyl groups regulate the Zn content. 2+ Uniform flux; hydrophobic alkyl groups repel free water molecules and suppress water-induced side reactions.
[0009] Compared to water molecules, organic anions have a smaller leading orbital energy difference, resulting in higher adsorption energy on zinc metal surfaces. These organic anions also exhibit a high binding energy with zinc ions, enabling them to enter the original solvation sheath structure of zinc ions ([Zn(H₂O)₆)). 2+This allows a water molecule to be replaced by an organic anion, forming a new solvation sheath structure that can reduce the desolvation energy of zinc ions.
[0010] Preferably, the organic anionic salt is a sodium salt containing a carboxylate group.
[0011] Preferably, the sodium salt containing the carboxylate group is selected from sodium 2-hydroxybutyrate or sodium glycolate.
[0012] Preferably, the concentration of the zinc salt electrolyte in the mixed aqueous solution is 0.5-2.0 mol / L. -1 The concentration of the organic anionic salt in the mixed aqueous solution is 0.1-2.0 g / L. -1 .
[0013] Preferably, the concentration of the zinc salt electrolyte in the mixed aqueous solution is 1 mol / L. -1 The concentration of the organic anionic salt in the mixed aqueous solution is 0.5 g / L. -1 .
[0014] This solution also provides a method for preparing the electrolyte based on the organic anion-mediated gradient ion pump regulating the interfacial reaction, including the following steps:
[0015] Dissolve zinc salt in deionized water and stir until completely dissolved to obtain zinc salt electrolyte; add organic anionic salt to zinc salt electrolyte and stir ultrasonically to obtain the electrolyte solution.
[0016] Preferably, the ultrasonic stirring time is 30 min.
[0017] This solution also provides an aqueous zinc metal battery based on an organic anion-mediated gradient ion pump to regulate interfacial reactions, including a zinc anode, a cathode, a separator, and the aforementioned electrolyte based on an organic anion-mediated gradient ion pump to regulate interfacial reactions.
[0018] In air, coin cells or pouch cells are assembled in the following order: zinc negative electrode → separator → electrolyte → positive electrode. The coin cells are model CR2032, and the pouch cells are 3 × 3 cm. 2 The electrode size is specified, and the electrolyte volume for the coin cell is 80 μL. After encapsulation, the cells are left to stand for 12 hours for later use.
[0019] The aqueous electrolyte containing organic anionic salts uses zinc salt aqueous solution as the reference electrolyte and adds organic anionic salts as functional additives. During battery cycling, a gradient ion pump solid electrolyte interface is formed in situ on the surface of the zinc anode. The interface has an organic / inorganic hybrid layered structure, with an outer layer of amorphous organic / ZnCO3 and an inner layer of organic / ZnCO3 / ZnO / ZnS. Organic anions exhibit a gradient distribution characteristic within this organic / inorganic hybrid layered structure.
[0020] The zinc anode uses zinc foil, zinc alloy foil, or zinc-based composite materials. During battery cycling, a gradient ion pump solid electrolyte interface is formed in situ on the anode surface.
[0021] Preferably, the preparation process of the positive electrode includes: mixing positive electrode active material, conductive agent, and binder, adding N-methylpyrrolidone to form a slurry, uniformly coating it on a carbon paper current collector, and obtaining a positive electrode sheet after vacuum drying.
[0022] More preferably, the vacuum drying temperature is 80 °C and the drying time is 12 h;
[0023] Preferably, the positive electrode active material is selected from commercially available MnO2 powder or V2O5; the conductive agent is selected from acetylene black; and the binder is selected from polyvinylidene fluoride.
[0024] The mass ratio of the positive electrode active material to the conductive agent and binder is 8:1:1.
[0025] Preferably, the diaphragm is selected from any one of glass fiber diaphragm, polypropylene diaphragm or cellulose diaphragm.
[0026] The technical solution of this invention has one or more of the following beneficial technical effects:
[0027] (1) High reversibility and long cycle life: This invention utilizes a gradient ion pump constructed with organic anions to achieve an average coulombic efficiency greater than 99% for Zn / / Ti asymmetric cells and a long cycle life of Zn / / Zn symmetric cells at 1 mA cm⁻¹. -2 (0.5 mAh cm) -2 Under these conditions, the cycle life exceeds 2000 h, 20 mA cm⁻¹ -2 It can still cycle stably for over 800 hours at high rates; the Zn / / MnO2 full cell retains nearly 100% capacity after 10,000 cycles at 10C rate, which is significantly better than existing electrolyte additive technology.
[0028] (2) Highly efficient suppression of side reactions: The dynamic Janus interface constructed by organic anions and the solvation reconstruction effect can reduce the corrosion current density of the zinc anode from 2.82 mA cm⁻¹. -2 Decreased to 0.98 mA cm -2 At the same current density (10 mA cm⁻¹) -2 The hydrogen evolution potential was increased from 1.11 V to 1.16 V, while the accumulation of byproducts was suppressed and the interfacial resistance was reduced.
[0029] (3) Low cost and practicality: The amount of organic salt added is very low, only 0.1-2.0 g / L. -1 The preparation process is simple, requires no complex equipment, and is easy to scale up for production.
[0030] (4) Excellent practical application performance: The Zn / / MnO2 small soft pack battery based on the present invention can be stably cycled more than 400 times at 3C rate and retain more than 90% of its capacity. Three soft pack batteries connected in series can light up more than 150 red LEDs, which has practical application potential.
[0031] Furthermore, other beneficial effects of the present invention will be mentioned in the specific embodiments. Attached Figure Description
[0032] Figure 1 The working principle of electrolyte additives;
[0033] Figure 2 This is a schematic diagram of the structure of the organic anionic additive selected for this invention;
[0034] Figure 3 The pH, viscosity, and conductivity of the zinc sulfate electrolyte and the electrolyte with added organic anionic additives selected for this invention;
[0035] Figure 4 The frontier orbital energies of the organic anionic additive and water molecules selected for this invention and their schematic diagrams;
[0036] Figure 5 The adsorption energies of the organic anionic additive and water molecules selected for this invention on the zinc
[002] crystal plane and their adsorption schematic diagram;
[0037] Figure 6 The diagram shows the binding energy of the organic anionic additive and water molecules with zinc ions selected for this invention.
[0038] Figure 7 Molecular dynamics simulations of the zinc sulfate electrolyte and the electrolyte with added BA additive selected for this invention, as well as schematic diagrams of the zinc ion solvation structure in the solution;
[0039] Figure 8 These are scanning electron microscope images of the zinc anode in Example 5 of this invention after cycling in ZnSO4 and ZnSO4+BA electrolytes;
[0040] Figure 9 The image shown is a transmission electron microscope image of the zinc anode in Example 5 of this invention after cycling in ZnSO4 and ZnSO4+BA electrolytes.
[0041] Figure 10 This is an XPS depth profile of the zinc anode in Example 5 of the present invention after cycling in ZnSO4 and ZnSO4+BA electrolytes;
[0042] Figure 11This is the time-of-flight secondary mass spectrum of the zinc anode in Example 5 of the present invention after cycling in ZnSO4+BA electrolyte;
[0043] Figure 12 The Tafel curves and linear sweep cyclic voltammetry curves of the zinc anode in ZnSO4 and ZnSO4+BA electrolytes in Example 5 of this invention are shown.
[0044] Figure 13 Electrochemical impedance spectroscopy of the zinc anode in ZnSO4 and ZnSO4+BA electrolytes in Example 5 of this invention;
[0045] Figure 14 Electrochemical performance of the Zn / / Zn symmetric cell and the Zn / / Ti asymmetric cell of the present invention in ZnSO4 and ZnSO4+BA electrolytes;
[0046] Figure 15 The electrochemical performance of the Zn / / MnO2 battery of the present invention in ZnSO4 and ZnSO4+BA electrolytes is shown. Detailed Implementation
[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0048] To address the inherent contradiction between low conductivity of organic components in existing technologies and the difficulty in balancing interfacial resistance and efficient ion migration, this solution provides an electrolyte based on an organic anion-mediated gradient ion pump to regulate interfacial reactions. The electrolyte comprises a mixed aqueous solution of a zinc salt electrolyte and an organic anionic salt. The zinc salt electrolyte is selected from any one of zinc sulfate, zinc chloride, zinc acetate, or zinc trifluoromethanesulfonate. The organic chain in the organic anionic salt has a Janus structure and contains hydroxyl groups and hydrophobic alkyl groups at the end of the chain.
[0049] In the above electrolyte, organic anionic salts achieve multiple functions through electrostatic adsorption and molecular coordination:
[0050] A Janus-like transport channel is formed at the zinc anode interface: organic anions electrostatically bind to the zinc surface, and hydroxyl groups regulate Zn. 2+ Uniform flux; hydrophobic alkyl groups repel free water molecules and suppress water-induced side reactions;
[0051] Reconstructing Zn 2+Solvated sheath: Organic anions replace some water molecules in the first solvated sheath (PSS) to form a water-poor solvated structure, lowering the desolvation energy barrier, and simultaneously reorganizing the hydrogen bond network of water molecules to reduce the free water content.
[0052] The organic anion-mediated gradient ion pump-regulated interface GIP-SEI has an organic / inorganic hybrid layered structure: the outer layer is an amorphous organic / ZnCO3 layer, and the inner layer is an organic / ZnCO3 / ZnO / ZnS layer; this interface phase has organic gradient distribution characteristics, which can promote Zn 2+ Rapid migration, while inhibiting zinc dendrite growth and hydrogen evolution reaction.
[0053] The working principle of electrolyte additives is as follows Figure 1 As shown, Figure 1 This study demonstrates how an organic anion (e.g., 2-hydroxybutyrate (BA))-mediated gradient ion pumping enhances the reversibility of the zinc anode. The electrochemical reactions at the zinc anode involve complex redox reactions during zinc deposition / stripping. During deposition, BA is primarily adsorbed onto the zinc surface via electrostatic interactions of carboxyl groups, forming a Janus-like interface. Within this interfacial phase, hydroxyl groups regulate the Zn... 2+ The flux is high, while the terminal hydrophobic methyl group repels free water molecules, thereby guiding uniform zinc deposition while suppressing water-induced corrosion and hydrogen evolution side reactions. Furthermore, due to Zn... 2+ BA has a strong affinity for organic anions and can replace Zn. 2+ Water molecules in the first solvated sheath (PSS) form a water-poor solvation structure, promoting Zn 2+ Rapid desolvation. Organic anions also reduce free water content by recombinating hydrogen bond networks through electrostatic interactions with surrounding water molecules, further inhibiting HER and corrosion reactions.
[0054] The synergistic effect of deposition and stripping processes facilitates the in-situ formation of an SEI layer with an organic anion gradient distribution above a uniformly deposited zinc layer. For example... Figure 1 As shown, the organic / inorganic hybrid SEI consists of an outer amorphous BA / ZnCO3 layer and an inner BA / ZnCO3 / ZnO / ZnS layer. This gradient SEI acts as an ion pump, promoting the growth of ZnO and ZnO ions. 2+ Rapid transport, effective suppression of side reactions, and prevention of zinc dendrite formation. The establishment of these ion channels enables a highly reversible zinc deposition / stripping process.
[0055] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0056] Example 1: Preparation of sodium lactate-containing electrolyte
[0057] Weigh ZnSO4 and add it to 100 mL of deionized water. Stir magnetically for 30 min until completely dissolved to obtain 1 mol L. -1 The ZnSO4 standard electrolyte was used; then sodium lactate was weighed and added to the standard electrolyte, and ultrasonically stirred for 30 min to ensure uniform dispersion of sodium lactate, thus preparing a solution containing 0.5 g / L of sodium lactate. -1 The mixed electrolyte has a pH of 4.2.
[0058] Example 2: Preparation of electrolyte containing sodium 2-hydroxybutyrate
[0059] Weigh ZnSO4 and add it to 100 mL of deionized water. Stir magnetically for 30 min until completely dissolved to obtain 1 mol L. -1 The ZnSO4 standard electrolyte was used; then sodium 2-hydroxybutyrate was weighed and added to the standard electrolyte, and ultrasonically stirred for 30 min to ensure uniform dispersion of sodium 2-hydroxybutyrate, thus preparing a solution containing 0.5 g / L of sodium 2-hydroxybutyrate. -1 The mixed electrolyte has a pH of 4.15.
[0060] Example 3: Preparation of sodium glycolate-containing electrolyte
[0061] Weigh ZnSO4 and add it to 100 mL of deionized water. Stir magnetically for 30 min until completely dissolved to obtain 1 mol L. -1 The ZnSO4 standard electrolyte was prepared; then sodium glycolate was weighed and added to the standard electrolyte, and ultrasonically stirred for 30 min to ensure uniform dispersion of sodium glycolate, thus preparing a solution containing 0.5 g / L of sodium glycolate. -1 The mixed electrolyte has a pH of 4.4.
[0062] Example 4: Preparation of sodium acetate-containing electrolyte
[0063] Weigh ZnSO4 and add it to 100 mL of deionized water. Stir magnetically for 30 min until completely dissolved to obtain 1 mol L. -1The ZnSO4 standard electrolyte was prepared; then sodium acetate was weighed and added to the standard electrolyte, and ultrasonically stirred for 30 min to ensure uniform dispersion of sodium acetate, thus preparing a solution containing 0.5 g / L of sodium acetate. -1 The mixed electrolyte has a pH of 4.25.
[0064] Example 5: Assembly and Testing of Zn / / Zn Symmetrical Cells
[0065] Battery assembly: In air, using two zinc foils of the same size (1.54 cm) 2 A CR2032 coin cell was assembled using a 50 μm thick electrolyte as the positive and negative electrodes, a glass fiber separator as the separator, and the electrolytes prepared in Example 2 containing sodium 2-hydroxybutyrate and the ZnSO4 reference electrolyte without sodium 2-hydroxybutyrate as the electrolytes.
[0066] Electrochemical tests were performed on the assembled batteries, and material characterization and electrochemical testing were conducted on the zinc foil.
[0067] Cyclic stability testing was performed using the LANDCT2001A battery testing system, with constant current cycling tests conducted at different current densities and areal capacities.
[0068] Example 6: Assembly and Testing of Zn / / Ti Asymmetric Cells
[0069] Battery assembly: In an argon-filled glove box, two pieces of titanium foil and zinc foil of the same size (1.54 cm) were used. 2 A CR2032 coin cell was assembled using a 50 μm thick electrolyte as the positive and negative electrodes and a glass fiber separator as the separator. The electrolyte was prepared in Example 2 with sodium 2-hydroxybutyrate and ZnSO4 reference electrolyte without sodium 2-hydroxybutyrate, respectively. The cells were then tested after standing for 12 h.
[0070] Cyclic stability test: The LANDCT2001A battery test system was used to conduct constant current cycle tests under different current densities and areal capacities.
[0071] Example 7: Assembly and performance testing of Zn / / MnO2 button cells
[0072] Cathode preparation: Weigh 16 mg MnO2 (commercially available, particle size 50-100 nm), 2 mg acetylene black conductive agent, and 2 mg PVDF binder, add 1 mL NMP, and stir for 4 h to form a uniform slurry; coat the slurry onto carbon paper, with a coating area of approximately 4 cm². 2 The coated carbon paper was dried overnight in a vacuum drying oven at 80 ℃ to obtain the positive electrode sheet (active material loading of approximately 3 mg / cm³). -2 ).
[0073] Battery assembly: In air, using zinc foil (50 μm thick, 99.99% pure) as the negative electrode, glass fiber as the separator, and sodium 2-hydroxybutyrate electrolyte prepared in Example 2 as the electrolyte (electrolyte volume 80 μL), CR2032 coin cells were assembled in the following order: negative electrode shell → zinc negative electrode → separator → electrolyte → positive electrode plate → spring plate → positive electrode shell. After standing for 12 h, performance testing was performed.
[0074] Cyclic voltammetry (CV) testing: An electrochemical workstation (AUTOLAB PGSTAT302N) was used at a scan rate of 0.2 mV / s. -1 Voltage range: 0.8-1.9V.
[0075] Rate performance testing: The battery testing system (LANDCT2001A) was used to test the charge and discharge capacity at 1C, 2C, 3C, 5C, and 10C rates (1C = 308 mA g). -1 ).
[0076] Long-term cycling test: Cyclic test at 10C rate.
[0077] Example 8: Preparation and Practical Application Testing of Zn / / MnO2 Soft-Pack Batteries
[0078] Pouch cell fabrication: The positive electrode sheet has a size of 3 × 3 cm. 2 (Active substance loading approximately 3 mg cm) -2 The negative electrode uses a 3 × 3 cm electrode. 2 The electrolyte consisted of zinc foil, glass fiber as a diaphragm, and sodium 2-hydroxybutyrate electrolyte prepared in Example 2. The electrolyte volume was approximately 0.5 mL cm⁻¹. -2 The Zn / / MnO2 soft-pack battery was obtained by encapsulating it in air using a soft-pack battery encapsulation machine.
[0079] Cyclic performance: Cyclic tests were conducted at a 3C rate.
[0080] The structures of the organic anionic additives in Examples 1-4 are as follows: Figure 2 As shown, the effectiveness of organic anionic additives such as sodium glycolate (GA), acetate (AA), lactate (LA), and 2-hydroxybutyrate (BA) in improving the stability of zinc anodes is related to various physicochemical factors, including pH, viscosity, ionic conductivity, coordination strength, and adsorption capacity. Figure 3As shown, compared with other anionic additives, BA exhibits suitable viscosity and ionic conductivity, indicating its potential to improve zinc ion transport kinetics. The coordination of the anionic additive with zinc ions and its adsorption capacity on the zinc metal surface were calculated using density functional theory (DFT). Theoretically, during coordination and adsorption, the additive will interact with Zn... 2+ / Zn shares electrons, in which the molecule's electron-donating / electron-accepting ability plays a crucial role. According to frontier molecular orbital theory ( Figure 4 The band gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) reflects the electron-donating / accepting ability; a smaller band gap indicates a stronger ability. Based on DFT calculations, BA has a relatively small HOMO-LUMO band gap, indicating its ability to bind Zn. 2+ It exhibits excellent performance in terms of ion adsorption onto the zinc surface and formation of an organic / inorganic hybrid SEI film on the zinc surface via redox reactions. Importantly, the lowest LUMO energy level of BA indicates its susceptibility to electron gain, thereby promoting its adsorption on the zinc surface. Figure 5 The adsorption energy calculations further validated this. Compared to H₂O, BA has a lower HOMO level, indicating its adsorption capacity is lower than that of Zn. 2+ The strong coordination ability of BA confirms that it has the ability to regulate Zn. 2+ The first solvation shell promotes Zn 2+ Desolvation capability Figure 6 The binding energy data also corroborate this conclusion. In summary, considering the overall regulatory effect of BA, we selected it as the optimal electrolyte additive and systematically studied the regulatory mechanism of anionic additives in aqueous zinc metal batteries.
[0081] Zn was studied using MD simulation. 2+ Solvated structures. For example... Figure 7 Figure a shows the ZnSO4 solution system. Figure 7 As described in b, in the BA-modified system, the organic anion portion enters Zn. 2+ The first solvation shell of Zn replaces a water molecule to form a new solvation shell containing organic anions. Therefore, the addition of organic anions can make Zn... 2+ The formation of a water-poor solvated structure lowers the desolvation energy barrier, effectively suppresses water-induced parasitic reactions, and enhances Zn content. 2+ Interface transport dynamics.
[0082] Scanning electron microscopy (SEM) revealed the morphological evolution of zinc anodes in different electrolytes under different cycling cycles. For example... Figure 8As shown, after 20 cycles in the ZnSO4 electrolyte, the zinc anode surface became rough and developed fine agglomerates and protrusions. With increasing cycle count, severe side reactions produced a large number of byproducts, and noticeable cracks appeared on the electrode surface. In contrast, the zinc anode circulated in the ZnSO4+BA electrolyte maintained a smooth and flat morphology even after 100 cycles.
[0083] High-resolution transmission electron microscopy (HRTEM) further analyzed the microstructure of the deposited zinc and SEI. The electrode circulated in ZnSO4 electrolyte exhibited a rough SEI layer, consisting of a thick amorphous outer layer and a crystalline inner layer, indicating severe corrosion and electrolyte decomposition. Conversely, the electrode circulated in BA-containing electrolyte showed a smooth SEI surface. Figure 9 Subsequent analysis confirmed that the amorphous outer layer of both electrodes was a ZnCO3-rich material. This smooth SEI layer facilitates a uniform surface electric field distribution, thereby improving the reversibility and stability of zinc deposition / stripping.
[0084] X-ray photoelectron spectroscopy (XPS) combined with argon ion (Ar⁺) sputtering (0 s, 100 s, 200 s) analyzed the chemical composition of the formed SEI layer. High-resolution C1s spectra ( Figure 10 (b) shows characteristic peaks for CO and OC=O bonds. Notably, after 200 s sputtering, the binding energy of the OC=O bond in the BA-containing sample showed a significant blue shift, indicating that the BA organic molecule is embedded in the SEI structure; however, this shift was not observed in the zinc anode cyclic in ZnSO4 electrolyte. Figure 10 (a).
[0085] To directly detect the spatial distribution of the SEI layer on the zinc anode circulating in ZnSO4+BA electrolyte, time-of-flight secondary ion mass spectrometry (TOF-SIMS) was used for further in-depth analysis. Figure 11The 3D distribution of characteristic ionic fragments (SO3⁻, ZnO⁻, CH⁻, ZnS⁻, CO3⁻, and OH⁻) is shown, with the signal intensity of these fragments gradually decreasing with increasing depth. Notably, the TOF-SIMS images reveal a non-uniform spatial distribution of these species, consistent with previously reported gradient composition distributions in aqueous zinc anodes. Combining XPS and TOF-SIMS data reveals the formation of an oxygen-rich, zinc-loving SEI layer at the zinc interface. This hybrid SEI exhibits a distinct layered structure: the outer layer is primarily composed of ZnSO4, BA additives, and ZnCO3, while the inner layer closer to the zinc metal is dominated by zinc-based inorganic compounds (such as ZnO, Zn(OH)2, and ZnS). Crucially, the signal intensity of BA-derived molecules gradually decreases with increasing Ar⁺ etching depth. Overall, these interpenetrating, gradient-distributed functional BA molecules, combined with the inorganic components, form a stable and dense SEI layer. This engineered SEI acts as a highly efficient ion pump, ensuring Zn deposition / stripping. 2+ It can transmit without obstruction.
[0086] Figure 12 The electrochemical corrosion and hydrogen evolution reaction of the zinc anode in different electrolytes are shown. Figure 12 As shown in Figure a, the corrosion current density calculated using Tafel curve testing is 2.82 mA cm⁻¹ in the ZnSO₄ electrolyte. -2 Significantly reduced to 0.98 mA cm⁻¹ after adding BA additive. -2 This indicates that the zinc anode exhibits significantly enhanced corrosion resistance in the ZnSO4+BA electrolyte. Furthermore, Figure 12 The linear sweep voltammetry shown in b indicates that, at the same current density, the electrolyte containing BA additive has a more negative potential, confirming the inhibitory effect of BA additive on the hydrogen evolution reaction at the zinc anode.
[0087] Electrochemical impedance spectroscopy reveals the chemical corrosion of the zinc anode in different electrolytes. For example... Figure 13 As shown, in the ZnSO4 electrolyte, due to the formation of loose byproducts, the impedance of the Zn / / Zn symmetric cell after standing for 3 days exceeds five times the initial value. However, in the designed ZnSO4+BA electrolyte, although an increase in charge transfer impedance due to the formation of a dense protective film was also observed after 3 days of standing, its value was significantly lower than that of the cell in the ZnSO4 electrolyte. This indicates that the formed protective film acts as a barrier to active water and ensures excellent interfacial ion / electron transport.
[0088] To verify the advantages of BA in stabilizing the zinc anode, a Zn / / Zn symmetric cell was tested. At 1 mA cm⁻¹ -2 The current density and 0.5 mAh cm⁻¹ -2At the areal capacity, the zinc anode in the ZnSO4+BA electrolyte exhibits high reversible cycling performance, low voltage hysteresis, and a cycle life exceeding 2500 hours. Figure 14 (a) This enhanced stability is attributed to the gradient adsorption of BA molecules on the zinc surface, forming a thin SEI layer with high ionic conductivity, which maintains the stability of Zn. 2+ The rapid transport kinetics of the zinc electrolyte are evident; conversely, the zinc anode in the ZnSO4 electrolyte short-circuit after only 300 hours of cycling.
[0089] Rate performance testing of symmetrical Zn / / Zn cells revealed that at 0.5 mA cm⁻¹… -2 up to 200 mA cm -2 Under test conditions (such as) Figure 14 (b) The battery potential change is more pronounced in the pure ZnSO4 electrolyte, while the battery in the ZnSO4+BA electrolyte exhibits a lower potential change, indicating that the addition of BA additive can effectively improve the rate performance of the battery. By analyzing the potential changes in the two electrolytes, combined with the exchange current ( Formula 1: (Equation 1), where i, η, F, R, and T represent the test current density, overpotential, Faraday constant, gas constant, and absolute temperature, respectively. For example... Figure 14 After adding BA additive to c, The significant increase indicates that the interfacial charge transfer kinetics in the ZnSO4+BA electrolyte have been improved.
[0090] Furthermore, the reversibility and stability of the zinc deposition / stripping process were evaluated using Zn / / Ti asymmetric cells. Figure 14 As shown in d, the battery containing BA is at 1 mA cm⁻¹ -2 After 600 cycles, the average coulombic efficiency was greater than 99.0%, confirming that BA significantly improved interfacial reversibility and suppressed dendrite formation. Conversely, the coulombic efficiency of the battery in ZnSO4 electrolyte fluctuated severely and decreased rapidly after 100 cycles, due to parasitic side reactions and non-uniform nucleation and epitaxial growth of zinc. This significant difference in stability is also reflected in the corresponding voltage curves, with the battery using ZnSO4+BA electrolyte ( Figure 14 The stable voltage curve of (e) further illustrates the positive role of BA in optimizing interfacial reaction kinetics.
[0091] The compatibility of BA additive with the MnO2 cathode was evaluated in the assembled Zn / / MnO2 full cell, and its energy storage performance was assessed. The cyclic voltammetry (CV) curves of the assembled Zn / / MnO2 battery showed two characteristic redox peaks, corresponding to the intercalation / deintercalation reaction of H⁺ / Zn²⁺. Figure 15(a) Compared with pure ZnSO4 electrolyte, the redox peak positions of the Zn / / MnO2 battery with BA additive showed almost no shift, indicating that the addition of BA does not change the basic redox reaction mechanism of MnO2. Notably, the area enclosed by the CV curve increased significantly after the addition of BA, indicating that the capacity of the Zn / / MnO2 battery was improved.
[0092] Rate performance tests were conducted at progressively increasing current rates from 1C to 10C (followed by a gradual return to 1C). The results confirmed that the electrolyte with added BA achieved higher capacity at all current densities. Figure 15 (b) Compared with the additive-free system, ZnSO4+BA electrolyte exhibits superior rate performance.
[0093] Impedance tests were performed on Zn / / MnO2 cells in different electrolytes at open-circuit potential, such as... Figure 15 As shown in Figure c, the charge transfer impedance of the battery containing the additive BA is significantly reduced, indicating that MnO2 has good electronic and ionic conductivity in this electrolyte.
[0094] The long-term cycle stability of Zn / / MnO2 batteries in different electrolytes is as follows: at 10C ( Figure 15 (d) The ZnSO4+BA electrolyte battery exhibited excellent stability, with its capacity still higher than the initial value after 10,000 cycles and its coulombic efficiency close to 100%. In contrast, the pure ZnSO4 electrolyte battery showed significant fluctuations in coulombic efficiency and capacity after about 2,800 cycles and failed after 8,000 cycles. This was due to the dissolution of MnO2 under weakly acidic conditions and the soft short circuit inside the battery.
[0095] Using 3×3 cm 2 Actual testing of the pouch battery showed that, under 3C conditions, its capacity was 89.2 mAh g. -1 After 460 cycles, it still retains 92.8% of its maximum capacity. Figure 15 These results confirm that BA, by constructing a GIP-SEI to regulate interfacial kinetics, can effectively suppress side reactions and accelerate Zn. 2+ Migration, thereby improving battery capacity and cycle stability.
[0096] In summary, during zinc deposition / stripping, organic salt anions with multiple zinc-philic groups (carboxyl and hydroxyl groups) and terminal hydrophobic methyl groups adsorb onto the zinc surface, forming Janus-like transport channels. These channels can promote Zn deposition / stripping. 2+ It can increase flux and inhibit active water molecules, while the partial desorption and dissociation of organic salts further promote the formation of GIP-SEI.
[0097] In summary, the strongly adsorbed organic salt anions form a dynamic Janus interface, promoting unimpeded migration of Zn²⁺ while preventing water molecule contact. During cycling, the organic salt undergoes adsorption, partial desorption, and dissociation, achieving interface self-repair. Simultaneously, in the bulk electrolyte, the coordinating organic salt anions modify the Zn²⁺ solvation structure, promoting desolvation during deposition and temporarily capturing Zn²⁺ during stripping. Therefore, the zinc anode with added organic salt achieves a coulombic efficiency of up to 99.6% and excellent cycle stability (over 2500 hours); the assembled Zn / / MnO₂ full cell exhibits excellent rate performance and long-term cycle stability (over 10,000 cycles). This approach provides new insights into the electrolyte design principles of AZMBs and offers new mechanistic insights for developing stable aqueous battery systems.
[0098] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. Electrolyte for the control of interfacial reactions based on organic anion-mediated gradient ion pumps, characterized in that, The electrolyte comprises a mixed aqueous solution of zinc salt electrolyte and organic anion salt; The zinc salt electrolyte is selected from any one of zinc sulfate, zinc chloride, zinc acetate or zinc triflate; The organic chain of the organic anion salt is Janus structure, and the organic chain contains hydroxyl and hydrophobic alkyl end chain.
2. The electrolyte based on organic anion-mediated gradient ion pump-regulated interface reactions according to claim 1, characterized in that, The organic anion salt is sodium salt containing carboxylate.
3. The electrolyte based on organic anion-mediated gradient ion pumping to regulate interface reactions according to claim 2, characterized in that, The sodium salt containing carboxylate is selected from sodium 2-hydroxybutyrate or sodium glycolate.
4. The electrolyte for interface reaction control based on organic anion-mediated gradient ion pumping according to claim 1, wherein the concentration of the zinc salt electrolyte in the mixed aqueous solution is 0.5-2.0 mol L -1 ; the concentration of the organic anion salt in the mixed aqueous solution is 0.1-2.0 g L -1 .
5. The electrolyte for interface reaction control based on organic anion-mediated gradient ion pumping according to claim 1, wherein the concentration of the zinc salt electrolyte in the mixed aqueous solution is 1 mol L -1 ; the concentration of the organic anion salt in the mixed aqueous solution is 0.5 g L -1 .
6. The method for preparing an electrolyte based on the organic anion-mediated gradient ion pump-regulated interface reaction according to any one of claims 1 to 5, characterized in that, The method comprises the following steps: Dissolving the zinc salt in deionized water and stirring until completely dissolved to obtain the zinc salt electrolyte; adding the organic anion salt to the zinc salt electrolyte and stirring under ultrasonic to obtain the electrolyte.
7. An aqueous zinc metal battery based on organic anion-mediated gradient ion pump regulated interfacial reactions, characterized in that, The positive electrode is prepared by mixing the positive electrode active material, the conductive agent and the binder, adding N-methylpyrrolidone to make a slurry, uniformly coating the slurry on the carbon paper current collector, and vacuum drying to obtain the positive electrode.
8. The water-based zinc metal battery based on organic anion-mediated gradient ion pump regulated interface reaction according to claim 7, characterized in that, The positive electrode active material is selected from commercial MnO2 powder or V2O5; the conductive agent is selected from acetylene black; the binder is selected from polyvinylidene fluoride; and the mass ratio of the positive electrode active material to the conductive agent and the binder is 8:1:
1.
9. The water-based zinc metal battery based on organic anion-mediated gradient ion pump regulated interface reaction according to claim 8, characterized in that, The separator is selected from any one of glass fiber separator, polypropylene separator or cellulose separator.
10. The aqueous zinc metal battery based on organic anion-mediated gradient ion pump regulated interfacial reactions of claim 7, wherein,
Citation Information
Cited By
Mixed aqueous electrolyte containing long-chain fatty acid zinc salt and application thereof
CN122000496A
A mixed aqueous electrolyte containing a long-chain fatty acid zinc salt and applications thereof
CN122000496B